Acute Kidney Injury (AKI) Pasca Primary Coronary Intervention (PCI) pada Pasien STEMI - Gunawan, Erik Jaya; Isnaini, Isnaini; Siahaan, Salmon Charles P. T.; Setyawan, Yuswanto; Ritunga, Imelda (Universitas HKBP Nommensen, 2024)
Background: Treating STEMI with PCI not only has a positive impact on patients, but also the risk of complications. A complication that can occur is AKI. The aim of this case report is to increase clinician awareness by analyzing the risk of AKI after PCI in order to reduce patient morbidity and mortality rates. Case: A 58-years old-man, with a history of diabetes mellitus, dyslipidemia, and a previous heart attack, came to the emergency department because of chest pain. The patient experienced STEMI and received fibrinolytic therapy. After 3 days of treatment, the condition worsened and the patient experienced shortness of breath (pulmonary edema). The patient was referred to RSUD Dr. M. Soewandhie Surabaya to undergo PCI. Two days after PCI, there were clinical signs of AKI. The patient was prepared for Renal Replacement Therapy (RRT), but the patient experienced cardiac arrest and was declared dead. Discussion: AKI after PCI involves various complex mechanisms. Several factors that can increase the probability of AKI after PCI in this case are a history of diabetes mellitus, previous decline in kidney function, and pulmonary edema. Technique factors such as transfemoral PCI and the amount of contrast volume used also have an influence on the incidence of AKI after PCI and need to be studied further. Risk factors in patients can be used to determine clinical scores, such as the Mehran, ADVANCIS, or ACEF-MDRD scores to predict the probability of AKI after PCI. Conclusion: AKI after PCI is a frequent complication and calculations using clinical scores can be applied to predict this event.